2011
DOI: 10.1073/pnas.1100225108
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous revisitation during visual exploration as a link among strategic behavior, learning, and the hippocampus

Abstract: Effective exploratory behaviors involve continuous updating of sensory sampling to optimize the efficacy of information gathering. Despite some work on this issue in animals, little information exists regarding the cognitive or neural mechanisms for this sort of behavioral optimization in humans. Here we examined a visual exploration phenomenon that occurred when human subjects studying an array of objects spontaneously looked "backward" in their scanning paths to view recently seen objects again. This "sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
148
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(168 citation statements)
references
References 47 publications
15
148
4
Order By: Relevance
“…Accordingly, only conscious memories are thought to be flexibly integrated and expressed (Reber et al, 1996;Smith and Squire, 2005). However, these classic notions have been questioned by the finding of implicit inference (Greene et al, 2001(Greene et al, , 2006Leo and Greene, 2008), by the finding of an implicit expression of hippocampus-dependent memory indexed by eye movements (Hannula and Ranganath, 2009;Voss et al, 2011), and by the finding of unconscious association formation and retrieval with concurrent hippocampal activation (Henke et al, 2003a,b;Degonda et al, 2005). Our current findings extend these previous findings by showing that the exclusion of conscious awareness of encoding and retrieval does not abolish rapid relational integration or long-term storage or the flexible expression of memories in new contexts or task-related hippocampal computation.…”
Section: Retrieval (A-c ͼ A-d) Noactivationsmentioning
confidence: 95%
“…Accordingly, only conscious memories are thought to be flexibly integrated and expressed (Reber et al, 1996;Smith and Squire, 2005). However, these classic notions have been questioned by the finding of implicit inference (Greene et al, 2001(Greene et al, , 2006Leo and Greene, 2008), by the finding of an implicit expression of hippocampus-dependent memory indexed by eye movements (Hannula and Ranganath, 2009;Voss et al, 2011), and by the finding of unconscious association formation and retrieval with concurrent hippocampal activation (Henke et al, 2003a,b;Degonda et al, 2005). Our current findings extend these previous findings by showing that the exclusion of conscious awareness of encoding and retrieval does not abolish rapid relational integration or long-term storage or the flexible expression of memories in new contexts or task-related hippocampal computation.…”
Section: Retrieval (A-c ͼ A-d) Noactivationsmentioning
confidence: 95%
“…First of all, hippocampal tasks such as place navigation also involve other structures (Whishaw et al 1987;Packard et al 1994;Devan and White 1999;Voss et al 2011;Gruber and McDonald 2012). Although some studies have shown impairments in VTE and performance with hippocampal lesions (Hu and Amsel 1995), VTE has also been seen on hippocampusindependent tasks (Bett et al 2012).…”
Section: Vte Increases With Hippocampal Engagementmentioning
confidence: 99%
“…Neurophysiological studies support the hypothesis that during VTE an animal is using its "cognitive map" by internally representing potential pathways (Johnson and Redish 2007) and evaluating future outcomes (van der Meer and Redish 2010). Various studies have shown that VTE is supported by the hippocampus (Hu and Amsel 1995;Voss et al 2011), occurs early in learning (Tolman 1939;van der Meer and Redish 2010), and increases with changes in task demands (Blumenthal et al 2011). However, to date, it has been difficult to determine the degree to which VTE behavior is linked to the different decisionmaking systems available.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…At the very least, the neuronal apparatus serving spatial representation has been found in the human hippocampus 10 . Also, at the behavioral level, human saccade-fixate-saccade sequences have been reported during moments of decision-making in visuospatial tasks, suggesting that humans also project onto their possible options before taking a decision 11,12 . Thus, one could expect that similar to rodents, specific behavioral mechanisms take place during the various stages of spatial learning in the human model.…”
Section: Introductionmentioning
confidence: 99%